Przyjaźń (nie)doskonała w polsko- -bułgarskiej korespondencji Wilhelma Macha i Dymitra Dobrewa - Kovacheva, Adriana (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
The article presents Dimitar Dobrev’s perspectives on the literary work of Wilhelm Mach and his understanding of his friendship with the Polish author. The arguments are mainly based on forgotten materials documenting the relationship between Dobrev and Mach. The most interesting aspects of the friendship between the writers are those causing conflicts and misunderstandings. The authors disagree over the definition of realism and the role of literature in the contemporary world, and those differences are intensified by Dobrev’s and Mach’s opposite comprehension of the ideals of a socialist society. The paper’s main topic is how the discrepancies between Mach and Dobrev influence their style and – particularly in Mach’s case – how they affect his experimental prose. The disagreements between the writers are both frustrating and inspiring for them as authors and they also distort the perception of Mach’s work as presented for his Bulgarian readers in Dobrev’s essays.